The Innovative cluster organization of science, education and business integration as an effective mechanism to increase the competitiveness of economy (Journal of Economic Research & Business Administration, 2016)
This article discusses the conditions and prerequisites for creation and development of innovative clusters. The role of transnational corporations and universities, as participants in scientific, educational and innovative cluster. It was revealed that the integration of science, education and in dustry, on the example of the organization Biomedical cluster at the Al Farabi Kazakh National University, in a public private partnership is an effective mechanism innovation activity of the University, as a basis of the knowledge economy. Universities are becoming active subjects of trans national clusters, the intellectual centers of innovation, where human capi tal is concentrated.
Keywords: transnational cluster; innovative activity; innovative poli cy; university; education; transfer of technologies; publicprivate partner ship; concession; integration; medicine; competitiveness.